Kinerja Susut Pada Blok Beton Sandwich Dengan Isian Styrofoam - Natalia Desi Ratnawati; Irviana Dyah Permatasari; Rr.M.I Rretno Susilorini; David Widianto (Universitas Katolik Soegijapranata Semarang, 2017)
Shringkage is a volume change unrelated to the load, where the volume of concrete is reduceddue to reduced water content due to hydration or evaporation or evaporation. The objective ofthis research is to obtain the shrink parameter on sandwich block with Styrofoam stuffing inthe form of visual, damage, saturated and shrinkage in the medium of marine and freshwatersoak for 28 days and get the graph between time and depreciation. This research uses twoexperimental method that is by way of oven and not dioven in fresh water and marine waterimmersion media, each of which is submerged media in the form of 5 pieces of specimen length37 cm, width 15,5 cm, and thickness 7.5 cm which if in total amounted to 10 concrete blocks,the concrete block is tested in laboratory materials Soegijapranata Unika by using thecontainer as a medium of immersion media and the length of the sorong as a tool length, width,thickness of the block and the scale that has a precision of 0.1 for get the weight of the concretethen if it gets the result will result in the amount of shrinkage. The results obtained from theshrinkage will be concluded whether the sandwich panel with Styrofoam stuffing can be usedas a bearing wall.